The Pengaruh PMDN dan PMA terhadap Pertumbuhan PDRB Sumatera dengan Infrastruktur Telekomunikasi Perspektif Ekonomi Islam - Ardhi Anshori, Muhammad; Noviarita, Heni; Rosilawati, Weny (Li Falah: Journal of Islamic Economics and Business, 2026)
Regional economic growth in Sumatra continues to face disparities across provinces. Investment and telecommunications infrastructure are considered key drivers of economic performance. This study examines the effects of Domestic Investment(PMDN) and Foreign Direct Investment (PMA) on Gross Regional Domestic Product(GRDP) growth, with telecommunications infrastructure serving as a mediating variable from an Islamic economics perspective. Using a quantitative explanatory approach, this study analyzes panel data from ten provinces in Sumatra during 2015–2024, resulting in 100 observations. Data were obtained from BPS and the Ministry of Investment/BKPM and analyzed using panel data regression and Sobel mediation tests.The results show that PMDN, PMA, and telecommunications infrastructure significantly affect GRDP growth. Telecommunications infrastructure also mediates the relationship between investment and regional economic growth. These findings indicate that investment contributes more effectively to economic growth when supported by adequate infrastructure. The study provides insights for policies aimed at fostering inclusive and sustainable regional development in line with Islamic economic principles.